ANALISIS FAKTOR LINGKUNGAN TERHADAP KEBIASAAN BACA SISWA KELAS I SD 3 DEMAAN KUDUS - ., Sutarno; Fatmawati, Endang (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
The research objective was to determine the environmental factors that affect the reading habits of grade I students in Elementary School 3 Demaan Kudus. This research used a qualitative descriptive study with eleven informants consisting of the one class teacher, five students, and five students’ parents. The data sources are primary and secondary. Data collection techniques by observation, interviews, and literature study. Data analysis techniques with data reduction, data presentation, and concluding. The validity test used the source triangulation technique. The results showed that the reading habits of first-grade students at Elementary School 3 Demaan Kudus were influenced by the school environment and the home environment. School environmental factors such as social influence from friends, the class environment, rarely going to the school library, and not a special reading curriculum. Home environmental factors, namely the lack of parental attention, lack of parental motivation, and parents when at home have not provided an example to cultivate reading.